2015
DOI: 10.1038/srep18098
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Carbon Vacancies in Sub-stoichiometric ZrC1−x

Abstract: Sub-stoichiometric interstitial compounds, including binary transition metal carbides (MC1−x), maintain structural stability even if they accommodate abundant anion vacancies. This unique character endows them with variable-composition, diverse-configuration and controllable-performance through composition and structure design. Herein, the evolution of carbon vacancy (VC) configuration in sub-stoichiometric ZrC1−x is investigated by combining the cluster expansion method and first-principles calculations. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 48 publications
7
141
0
Order By: Relevance
“…In another study, a superlattice was identified using a combination of electrical resistivity, differential thermal analysis, and x‐ray diffraction (XRD) measurements on a specimen of ZrC 0.7 that was prepared by arc‐melting and annealing . Crystal structures of nonstoichiometric ZrC x have also been studied by computational methods, which predicted the stability of the Fd 3¯ crystal structure at carbon stoichiometries as low as x = 0.5 using mixing enthalpy calculations . Phase stability of highly carbon‐deficient compositions (eg, x ≤ 0.5) has been studied using formation enthalpy calculations, which showed that the Fd 3¯ structure, with ordered vacancies, was the most stable .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a superlattice was identified using a combination of electrical resistivity, differential thermal analysis, and x‐ray diffraction (XRD) measurements on a specimen of ZrC 0.7 that was prepared by arc‐melting and annealing . Crystal structures of nonstoichiometric ZrC x have also been studied by computational methods, which predicted the stability of the Fd 3¯ crystal structure at carbon stoichiometries as low as x = 0.5 using mixing enthalpy calculations . Phase stability of highly carbon‐deficient compositions (eg, x ≤ 0.5) has been studied using formation enthalpy calculations, which showed that the Fd 3¯ structure, with ordered vacancies, was the most stable .…”
Section: Introductionmentioning
confidence: 99%
“…We suppose that C atoms are fully occupying the 24e sites. Partial occupancy of the carbon sublattice can be important in some carbides 28,29 , but in this carbide we do not expect it to play a role of significance because the carbon vacancy formation enthalpy is very large (~1.05 eV/C vacancy) 30 .
Figure 1( a ) The γ-Cr 23 C 6 supercell consists of one conventional unit cells with four inequivalent metal sites, namely, the 4a, 8c, 32f, and 48h sites, according to Wyckoff notation. The C atoms are located at the 24e sites.
…”
Section: Introductionmentioning
confidence: 99%
“…20 was successfully applied to metals and non-polar semiconductors [1,6,12,14,23,28,33,34], the same strategy breaks down in the case of polar materials. In fact the singularity in Eq.…”
mentioning
confidence: 99%